Study of Hybrid PVA/MA/TEOS Pervaporation Membrane and Evaluation of Energy Requirement for Desalination by Pervaporation - Xie, Zongli (Int J Environ Res Public Health, 2018)
Desalination by pervaporation is a membrane process that is yet to be realized for commercial application. To investigate the feasibility and viability of scaling up, a process engineering model was developed to evaluate the energy requirement based on the experimental study of a hybrid polyvinyl alcohol/maleic acid/tetraethyl orthosilicate (PVA/MA/TEOS) Pervaporation Membrane. The energy consumption includes the external heating and cooling required for the feed and permeate streams, as well as the electrical power associated with pumps for re-circulating feed and maintaining vacuum. The thermal energy requirement is significant (e.g., up to 2609 MJ/m(3) of thermal energy) and is required to maintain the feed stream at 65 °C in recirculation mode. The electrical energy requirement is very small (<0.2 kWh/m(3) of required at 65 °C feed temperature at steady state) with the vacuum pump contributing to the majority of the electrical energy. The energy required for the pervaporation process was also compared to other desalination processes such as Reverse Osmosis (RO), Multi-stage Flash (MSF), and Multiple Effect Distillation (MED). The electrical energy requirement for pervaporation is the lowest among these desalination technologies. However, the thermal energy needed for pervaporation is significant. Pervaporation may be attractive when the process is integrated with waste heat and heat recovery option and used in niche applications such as RO brine concentration or salt recovery.